Trapped in the gap : doing good in Indigenous Australia - Kowal, Emma (Berghahn Books, 2015)
In Australia, a 'tribe' of white, middle-class, progressive professionals is actively working to improve the lives of Indigenous people. This book explores what happens when well-meaning people, supported by the state, attempt to help without harming. 'White anti-racists' find themselves trapped by endless ambiguities, contradictions, and double binds - a microcosm of the broader dilemmas of postcolonial societies. These dilemmas are fueled by tension between the twin desires of equality and difference: to make Indigenous people statistically the same as non-Indigenous people (to 'close the gap') while simultaneously maintaining their 'cultural' distinctiveness. This tension lies at the heart of failed development efforts in Indigenous communities, ethnic minority populations and the global South. This book explains why doing good is so hard, and how it could be done differently.